Impact of using supplemented thylakoids derived from spinach for 12 weeks of high-intensity functional training on adipo-myokines in obese males - Abbassi-Daloii, Asieh; Hoteit, Maha; Sadek, Zahra; Khak-Rand, Mahboubeh; Ramezani, Akbar; Pashaei, Zhaleh; Afshar, Mahsa; Escobar, Kurt A.; Supriya, Rashmi; Saeidi, Ayoub; Zouhal, Hassane; Alkhatib, Ahmad (Frontiers in Nutrition, 2025)
ObjectiveThis randomized controlled study investigated the independent and combined effects of High-Intensity Functional Training (HIFT) and spinach-derived thylakoid supplementation on adipo-myokines, glycemic control, and lipid profiles in obese males. To compare the effects of HIFT alone, thylakoid supplementation (Thyl) alone, and their combination (HIFT+Thyl) on circulating adipokines (CTRP-2, CTRP-9, GDF-8, GDF-15), insulin resistance, and lipid profiles in obese adult males.MethodsA total of 68 participants who were obese with BMI: 32.6 ± 2.6 kg/m2 were randomly assigned to four groups (n = 17 in each group): thylakoid supplementation (Thyl), HIFT + Placebo High-Intensity Functional Training (HIFT), HIFT + thylakoid supplementation (HIFT+Thyl), and control+Placebo group (C). The training groups (HIFT and HIFT+Thyl) completed a 12-week program of three 60-min sessions per week. Participants in the Thyl and HIFT+Thyl groups dissolved and consumed 5 g/day of spinach extract high in thylakoids (or placebo) for 12 weeks. Baseline and post-intervention measurements included circulating C1Q/TNF or TGF-β related proteins (CTRP-2, CTRP-9, GDF-8, GDF-15), insulin resistance (HOMA-IR, plasma glucose, and insulin), lipid profile (HDL-C, LDL-C, triglycerides [TG], total cholesterol [TC]), and body composition (BMI, fat mass [FM], and fat-free mass [FFM]). Randomization was performed using a block randomization method with allocation concealment.ResultsThere were significant group × time interactions for all variables (all p < 0.001): CTRP-9 (η2 = 0.6), CTRP-2 (η2 = 0.7), GDF-8 (η2 = 0.8), GDF-15 (η2 = 0.4), BMI (η2 = 0.45), FM (η2 = 0.42), HDL-C (η2 = 0.37), LDL-C (η2 = 0.34), TC (η2 = 0.46), TG (η2 = 0.66), insulin (η2 = 0.78), glucose (η2 = 0.5), and HOMA-IR (η2 = 0.7). Compared with baseline, all interventions (HIFT, Thyl, and HIFT+Thyl) significantly decreased adipokine levels (CTRP-9, CTRP-2, GDF-8, GDF-15), BMI, fat mass, LDL-C, TC, TG, insulin, glucose, and HOMA-IR, while increasing HDL-C (all p < 0.05). Post-hoc between-group comparisons showed that HIFT+Thyl resulted in significantly greater improvements in all adipo-myokines, lipid profile, glycemic and insulin control, and body fat compared to Thyl alone (all p < 0.05). HIFT and HIFT+Thyl showed comparable reductions in BMI, fat mass, and improvements in lipid profile and insulin sensitivity.ConclusionThese findings indicate that HIFT combined with spinach-derived thylakoid supplementation significantly decreases circulating adipo-myokines and improves insulin resistance and lipid profiles in obese adults, suggesting a promising lifestyle intervention for obesity management and cardiometabolic disease prevention. Further research is warranted to explore long-term effects and underlying mechanisms.Clinical Trial Registrationhttps://irct.behdasht.gov.ir/trial/69048, identifier (IRCT20151228025732N77).